Influence of media variations and growth regulators on in vitro propagation of Dendrocalamus asper bamboo - WAN NURFARZANA WAN MOHAMAD ZANI; NORRIZAH JAAFAR SIDIK; NUR AFIQAH MOHD ISA; ASMAH AWAL; NURUL IZZATI OSMAN; NORALIZA ALIAS; MOHD KHAIRI NORDIN (Nusantara Bioscience, 2024)
Abstract. Zani WNWM, Sidik NJ, Isa NAM, Awal A, Osman NI, Alias N, Nordin MK. 2024. Influence of media variations and growth regulators on in vitro propagation of Dendrocalamus asper bamboo. Nusantara Bioscience 16: 237-244. This study reports the effects of different types of media and combination of plant growth regulators on the in vitro propagation of Dendrocalamus asper (Schult.f.) Backer bamboo species, a species known for its economic significance and challenges in traditional cultivation. The experiment was initiated through the cultivation of in vitro nodal segments as explants in various strengths (half-strength and full-strength) of Murashige and Skoog’s (MS) and Vacin & Went (VW) media, supplemented with 1.0 mg L-1 6-benzylaminopurine (BAP) hormone. Optimal results were achieved in full-strength MS media with 1.0 mg L-1 BAP, with the highest shoot number (5.6 shoots) and length (2.14±0.18 cm), surpassing outcomes in VW media. Shoot multiplication in full-strength MS media, with varying BAP and indole-3-butyric acid (IBA) hormone combinations (0.5, 1.0, 2.0 and 4.0 mg L-1) was conducted, and the combination of 4.0 mg L-1 BAP and 0.5 mg L-1 IBA yielded the highest number of shoots (5.17±3.97), while supplementation with 4.0 mg L-1 IBA alone resulted in the longest shoot with 1.89±1.15 cm. These findings underscore the significance of tailored conditions for optimal in vitro propagation of this species. Further investigations could explore additional factors influencing the propagation process for better refinement of bamboo cultivation techniques.